Levels of Heavy Metals in Different Tissues of Pigeon (Columba livia) of Bangladesh for Safety Assessment for Human Consumption (Bangladesh Pharmaceutical Journal, 2013)
Heavy metal pollution was reported in commercially valuable and edible pigeon (Columba livia, Gmelin 1789) of Bangladesh. The concentrations of As, Pb, Cd, Cr, Zn, and Cu were investigated in the muscle, intestine, kidney, gizzard and liver. For this 60 C. livia were selected from five locations to assess the degree of pollution by heavy metals in pigeon. Significant differences in heavy metal concentrations were observed among different tissues, but not among the locations. The ranges of the measured concentrations (?g/g dry weight) in the tissues of C. livia were as follows: arsenic: (0.010.04), (0.020.04), (0.020.08), (0.020.04) and (0.030.07); lead: (0.210.56), (0.071.64), (0.621.97), (0.410.79) and (1.475.75); cadmium: (0.01-0.05), (0.130.97), (0.531.85), (0.32 0.78) and (0.222.41); chromium: (0.251.93), (1.185.90), (1.594.40), (1.151.65) and (1.388.36); zinc: (73.22256.56), (95.62130.75), (19.8767.18), (108.99124.77) and (159.80280.76); copper: (3.447.64), (5.3017.50), (8.7216.55), (1.1934.42) and (26.0943.60) in the muscle, intestine, kidney, gizzard, and liver, respectively. This research showed that the liver appeared to be the main storage site of heavy metals, while the muscle had the lowest levels of the analyzed metals. The concentrations of metal in the muscles were not found to exceed the acceptable level for human consumption. DOI: http://dx.doi.org/10.3329/bpj.v16i1.14499 Bangladesh Pharmaceutical Journal 16(1): 81-87, 2013